Structural quality in single crystalline CdSe ingots grown by PVT: Qualidade estrutural em lingotes de CdSe monocristalinos crescidos por PVT - D'Elía, Raúl Luis (2020)
CdSe is II-VI semiconductor with compact hexagonal structure. It has a band gap of 1.82 eV and a high stopping power for nuclear radiation. Single crystalline CdSe ingots were grown by Physical Vapor Transport (PVT) employing a horizontal reactor. As devices critically depend on material properties its single crystalline quality was determined by chemical etching and transmission electron microscopy. Results were compared to those corresponding to Bridgman High Pressure (HPB) grown material and also to PVT material grown in a vertical reactor.